2021
DOI: 10.26434/chemrxiv-2021-dvzv1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Localized Enantioselective Catalytic Site on Short DNA Sequences and their Amphiphiles

Abstract: A DNA-based artificial metalloenzyme (ArM) consisting of copper (II) complex of 4,4’-dimethyl-2,2’-bipyridine (dmbipy-Cu) bound to double-stranded DNA (dsDNA) as short as 8 base pairs with only two contiguous central G•C pairs (G for guanine and C for cytosine), catalyzes highly enantioselective Diels-Alder reaction in water. Molecular simulations indicate that these minimal sequences provide a single site where dmbipy-Cu is groove-bound and able to function as an enantioselective catalyst. Enantioselective pr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…It was reported that the modular DNA hybrid catalysts with appended PEG molecules or amphipathic lipids could work well under various organic solvent or water-organic co-solvent conditions. [111][112][113] By the generation of more robust DNA in the presence of beneficent organic solvents or the establishment of micellar catalysis, an even broader range of applications is feasible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that the modular DNA hybrid catalysts with appended PEG molecules or amphipathic lipids could work well under various organic solvent or water-organic co-solvent conditions. [111][112][113] By the generation of more robust DNA in the presence of beneficent organic solvents or the establishment of micellar catalysis, an even broader range of applications is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Although these water‐compatible biohybrid catalysts display remarkable activity under aqueous conditions, their application has been limited because most organic compounds are barely soluble in water, hesitating the use of DNA‐based hybrid catalysts. It was reported that the modular DNA hybrid catalysts with appended PEG molecules or amphipathic lipids could work well under various organic solvent or water‐organic co‐solvent conditions [111–113] . By the generation of more robust DNA in the presence of beneficent organic solvents or the establishment of micellar catalysis, an even broader range of applications is feasible.…”
Section: Discussionmentioning
confidence: 99%